Оптимизация параметров систем подрессоривания гусеничных машин (стохастический вариант) - Александров, Евгений Евгеньевич; Пидашов, В. В. (НТУ "ХПИ", 2005)
A parametric synthesis of suspension system of track vehicles with use of method of factorial experiment with account of casual micro profile of the road is described. Decision of stochastic task is revealed. It’s spoken about efficiency of the use of this method due to broad possibilities of parameters vari ation of suspension
Keywords: микро профиль дороги; подвеска гусеничных машин; функция регрессии; однородность дисперсии; транспортное гусеничное средство